1995
DOI: 10.1007/bf00019185
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of profilin from tobacco (Nicotiana tabacum): increased profilin expression during pollen maturation

Abstract: Profilin has recently been identified as an actin-binding protein in higher plants. A cDNA coding for tobacco profilin, which shared an average sequence identity of 75% with other plant profilins, was isolated from a tobacco pollen cDNA library by antibody screening. Tobacco profilin was expressed in Escherichia coli and purified by affinity to poly-(L-proline) Sepharose. A rabbit antiserum was raised against recombinant tobacco profilin and used to estimate the amount of profilin expressed in different tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 52 publications
4
57
0
3
Order By: Relevance
“…In general, plants contain many profilin isoforms; for example, Arabidopsis has five Kandasamy et al, 2002), maize (Zea mays) has at least five (Staiger et al, 1993;Gibbon et al, 1998;Kovar et al, 2001a), and tobacco (Nicotiana tabacum) has at least three (Mittermann et al, 1995). To identify how many profilin genes are present in P. patens, we searched the P. patens genome (http://genome.jgi-psf.org//Phypa1_1/ Phypa1_1.home.html) and found three profilin genes.…”
Section: P Patens Has Three Profilin Genesmentioning
confidence: 99%
“…In general, plants contain many profilin isoforms; for example, Arabidopsis has five Kandasamy et al, 2002), maize (Zea mays) has at least five (Staiger et al, 1993;Gibbon et al, 1998;Kovar et al, 2001a), and tobacco (Nicotiana tabacum) has at least three (Mittermann et al, 1995). To identify how many profilin genes are present in P. patens, we searched the P. patens genome (http://genome.jgi-psf.org//Phypa1_1/ Phypa1_1.home.html) and found three profilin genes.…”
Section: P Patens Has Three Profilin Genesmentioning
confidence: 99%
“…33 To examine whether they also contained other transcripts, RT-PCR analysis was performed. Several tobacco pollen-specific genes were tested including profilin, 39 actin depolymerizing factor 1 (ADF1), 40 eukaryotic translation initiation factors eIF4E, eIFiso4E 41 and R-tubulin A1 (accession number AJ421411; D. Brevario, direct submission). RT-PCR analysis revealed that all tested transcripts were present in the EPP fractions isolated by ultracentrifugation as well as directly from SEC ( Figure 3).…”
Section: Epps Contain Different Mrnasmentioning
confidence: 99%
“…Furthermore, several actin binding protein families, for example, actin depolymerizing factors and profilin, have been identified and cloned in pollen tubes (Staiger et al, 1993;Mitterman et al, 1995;Lopez et al, 1996;Vidali and Hepler, 1997;Yu et al, 1998). Although it is thought that pollen profilins play an important role in pollen tube growth by regulating microfilament formation, a thorough understanding of the regulation of actin dynamics and the exact role of the cytoskeleton in pollen tube growth is currently lacking.…”
Section: How It Is Made: Pollen Tube Growthmentioning
confidence: 99%